An Analysis of Illocutionary Acts in the Lights Out Movie by David F. Sandberg - Kartinawati Kartinawati (Program Studi Sastra Inggris Fakultas Ilmu Budaya Universitas Halu Oleo, 2017)
This research is about an analyze the illocutionary act in the Light Out movie using the theory of speech act by George Yule. This research focuses on analyzing the utterances of the woman character in the Light Out movie. This research aimed to find out the kinds of illocutionary acts uttered by the woman characters in the Lights Out movie by David F. Sanberg. The researcher used qualitative description because the data will take the form of utterances. The source of data in this research is the Lights Out movie and the data is utterances of the woman character which includes the kinds of illocutionary acts. The technique of data analysis is done by presenting the data, describing the data, and concluding the data. This research found that there are four kinds of illocutionary acts in the Lights Out movie that are representative, directive, commissive, and expressive. The researcher found there are 44 data in this research. There are 17 data from the representative, 17 data from the directive, 6 data from commissive, and 4 data from expressive. The kinds of illocutionary acts that are plenty used in the Lights Out movie are representative speech act and directive speech act and the least used is an expressive speech act.